Effect of an acrylic resin combined with an antimicrobial polymer on biofilm formation - Marra, Juliê; Paleari, André Gustavo [UNESP]; Rodriguez, Larissa Santana [UNESP]; Leite, Andressa Rosa Perin [UNESP]; Pero, Ana Carolina [UNESP]; Compagnoni, Marco Antonio [UNESP] (FapUNIFESP (SciELO), 2012)
Objectives: The purpose of this study was to evaluate the antimicrobial activity of an acrylic resin combined with an antimicrobial polymer poly (2-tert-butylaminoethyl) methacrylate (PTBAEMA) to inhibit Staphylococcus aureus, Streptococcus mutans and Candida albicans biofilm formation. Material and Methods: Discs of a heat-polymerized acrylic resin were produced and divided according to PTBAEMA concentration: 0 (control), 10 and 25%. The specimens were inoculated (107 CFU/mL) and incubated at 37°C for 48 h. After incubation, the wells were washed and each specimen was sonicated for 20 min. Replicate aliquots of resultant suspensions were plated at dilutions at 37°C for 48 h. The number of colony-forming units (CFU) was counted and expressed as log (CFU+1)/mL and analyzed statistically with α=.05. Results: The results showed that 25% PTBAEMA completely inhibited S. aureus and S. mutans biofilm formation. A significant reduction of log (CFU+1)/mL in count of S. aureus (control: 7.9±0.8A; 10%: 3.8±3.3B) and S. mutans (control: 7.5±0.7A; 10%: 5.1±2.7B) was observed for the group containing 10% PTBAEMA (Mann-Whitney, p<0.05). For C. albicans, differences were not significant among the groups (control: 6.6±0.2A; 10%: 6.6±0.4A; 25%: 6.4±0.1A), (Kruskal-Wallis, p>0.05, P=0.079). Conclusions: Acrylic resin combined with 10 and 25% of PTBAEMA showed significant antimicrobial activity against S. aureus and S. mutans biofilm, but it was inactive against the C. albicans biofilm.
Keywords: Acrylic resins; Biofilms; Dental materials; Polymers